Combining omics tools for the characterization of the microbiota of diverse vinegars obtained by submerged culture: 16S rRNA amplicon sequencing and MALDI-TOF MS - Román-Camacho, Juan J.; García-García, Isidoro; Santos-Dueñas, Inés M.; Ehrenreich, Armin; Liebl, Wolfgang; García-Martínez, Teresa; Mauricio, Juan C. (Frontiers in Microbiology, 2022)
Vinegars elaborated in southern Spain are highly valued all over the world because of their exceptional organoleptic properties and high quality. Among the factors which influence the characteristics of the final industrial products, the composition of the microbiota responsible for the process and the raw material used as acetification substrate have a crucial role. The current state of knowledge shows that few microbial groups are usually present throughout acetification, mainly acetic acid bacteria (AAB), although other microorganisms, present in smaller proportions, may also affect the overall activity and behavior of the microbial community. In the present work, the composition of a starter microbiota propagated on and subsequently developing three acetification profiles on different raw materials, an alcohol wine medium and two other natural substrates (a craft beer and fine wine), was characterized and compared. For this purpose, two different “omics” tools were combined for the first time to study submerged vinegar production: 16S rRNA amplicon sequencing, a culture-independent technique, and matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS), a culture-dependent method. Analysis of the metagenome revealed numerous taxa from 30 different phyla and highlighted the importance of the AAB genus Komagataeibacter, which was much more frequent than the other taxa, and Acetobacter; interestingly, also archaea from the Nitrososphaeraceae family were detected by 16S rRNA amplicon sequencing. MALDI-TOF MS confirmed the presence of Komagataeibacter by the identification of K. intermedius. These tools allowed to identify some taxonomic groups such as the bacteria genera Cetobacterium and Rhodobacter, the bacteria species Lysinibacillus fusiformis and even archaea, never to date found in this medium. These first findings may contribute to improving the understanding of the microbial communities' role in the vinegar-making industry.